"Splint" Mitral Valve Repair for Destructive Endocarditis in Children. Issue 1 (January 2019) - Gritti, Michael; Ferris, Anne; Shah, Amee; Bacha, Emile; Kalfa, David
Medical management of infective endocarditis in the pediatric population has an associated in-hospital mortality rate of up to 25%. In the past, infective endocarditis of the mitral valve was surgically managed with a valve replacement. Now, there is a shift toward repair. However, for complex lesions in pediatric patients, many institutions are still hesitant to perform a mitral valve repair. We describe the cases of three children with destructive mitral valve endocarditis and risk factors for higher perioperative mortality and morbidity who were successfully treated with a complex mitral valve repair with "splint" patch plasty of the posteromedial commissure.